Heterogeneidade de taxas de desconto e riqueza no Brasil: avaliação quantitativa através do modelo de Aiyagari - Oliveira, Diego da Costa (2023)
This thesis investigates the role of discount rate heterogeneity in wealth inequality, with a specic focus on Brazilian empirical data. Employing an extension of the Aiyagari (1994) model, we incorporate heterogeneity in agents’ discount factors, both in the form of xed yet heterogeneous rates and through a Markov stochastic process. This approach allows for the representation of economic agents with consumption and saving behaviors more aligned with those observed in Brazilian reality. We demonstrate that preference heterogeneity is a crucial factor in understanding the dynamics of wealth inequality, providing valuable insights for the development of effective economic policies. The proposed model, calibrated with conservative parameters, proved effective in replicating the observed wealth inequality in Brazil. We concludethat the introduction of heterogeneity in discount factors is essential to capture the complexity of economic dynamics and wealth distribution.